Study of Biological Activity for Some Extracts of Vitex agnus castus L - S. Chiad, Gamal; N. Jwad, Atlal; R. Abdulhameed, Hanan; F. Kamel, Abeer; M. Abdulla, Jassim (Iraqi Journal of Science, 2023)
The biological activity of vitex agnus castus L. was tested which including the following extracts: essential oil extract, methanol extract, (70%), ethanol extract( 70%), flavonoid extract and volatile oils extract were tested against many types of bacteria which are Staphylococus aureus , Bacillus pumilus, Escerichia coli,Pseudomonas, Enterobacter and Streptococcus sp., The results of this study showed difference activity of these extracts .The flavonoid extract considers the best activities which gave inhibition zone (20) mm on E. coli, Pseudomonas ; Staphylococus aureus of (15) mm on Bacillus pumilus and (9) mm on Streptococcus sp. Ethanol extract gave inhibition zone (15) mm on Staphylococus aureus, (11) mm on Streptococcus sp. (15) mm on Bacillus pumilus and (15) mm on Streptococcus sp.,while the essential oil extract did not have any antimicrobil activity.Fertility test was made in laboratory animals (mice) after confirming from toxicity test of alcoholic extract and, the results showed that this extract had effected on increasing the fertility for both males and females.The results of chemical tests of vitex agnus castus L. compounds showed contain tannins, carbohydrates, glycosides, phenols, resins, flavonoids, saponins and didn’t have alkaloids, proteins, steroids and cumarines